Modelling the Impact of Vaccination and Quarantine in the Dynamics of Mumps Infection with Hearing Loss - Khdr Ahmad, Karmand; Agaba, Grace O.; Rahman, Bootan (Tikrit Journal of Pure Science, 2025)
Hearing loss is a growing public health concern with serious implications for an individual's quality of life. This paper proposes a mathematical model that describes the dynamics of the spread of mumps and the associated risk of hearing loss caused by mumps infection. The model incorporates key epidemiological factors and considers the role of vaccination and quarantine as control measures. Mathematical analysis of the model was carried out to ensure positivity and boundedness of solutions over time. The model exhibits two steady states: a mumps-free steady state and a mumps-endemic steady state. Stability and sensitivity analyses show the effectiveness of quarantine and administering vaccine in minimizing the spread of mumps and consequently mitigating hearing loss. Though, quarantine has high significant impact on the dynamics with first dose of vaccination, the outcome after the second dose of vaccination is far better. In addition, the findings emphasize the importance of certain parameters in shaping the disease dynamics and offer guidance on effective intervention strategies. The study underscores the role of vaccination and quarantine in mitigating the impact of mumps-induced hearing loss.